Spatiotemporal variations of surface water microplastics near Kyushu, Japan: A quali-quantitative analysis. (August 2021) - Kobayashi, Tsunefumi; Yagi, Mitsuharu; Kawaguchi, Toshiya; Hata, Toshiro; Shimizu, Kenichi
Abstract: Microplastics in the ocean are threatening marine ecosystems. Although plastic contaminants are ubiquitous, their distribution is thought to be heterogeneous. Here, we elucidate the spatial and temporal variations in the quanti-qualitative characteristics of microplastics near Kyushu, Japan in the East China Sea. Six surveys across nine stations were conducted over a 14-month period, and a total of 6131 plastic items were identified. The average microplastic abundance and size were 0.49 ± 0.92 (items·m −3  ± S.D.), and 1.71 ± 0.93 (mm ± S.D.), respectively. Differences between the highest and lowest abundances were 50-fold among monthly means, and 550-fold across all net tows. With respect to colour, polymer type, and shape, white and transparent polyethylene fragments were the dominant composition. There were significant differences for each of the analytical microplastic parameters among the survey months. Our results provide baseline data and lead to a more comprehensive understanding of the spatiotemporal characteristics of microplastic pollution. Highlights: Spatiotemporal variability was detected based on the quali-quantitative analyses. Mean (±S.D.) MP abundance was 0.49 ± 0.92 (items·m −3 ) and size was 1.71 ± 0.93 (mm). Differences between highest and lowest abundances were 550-fold across all net tows. White and transparent polyethylene fragments were the dominant composition.